2023
DOI: 10.1021/acsestwater.2c00597
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Removal of Polyfluoroalkyl Substances by Simple Modified Biochar: Adsorption Performance and Theoretical Calculation

Abstract: To cope with the widespread polyfluoroalkyl substance (PFAS) pollution in the global aquatic environment, this study prepared an acid-modified biochar adsorbent derived from sludge with satisfactory performance. The theoretical maximum adsorption capacities of the adsorbent for perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) were determined to be 72.17 and 45.88 mg·g–1, respectively. The theoretical calculation of the adsorption of biochar surface functional groups with PFOS and PFOA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…For example, Zhang et al observed a blue-shift of nonaromatic ketone (C=O) peaks and new bands that were assigned to −CF 2 – before and after PFAS sorption by biochars using Fourier transform infrared spectrometry analysis. Similarly, density functional theory calculations confirmed that the C=O groups had the highest adsorption energy for PFAS . Nevertheless, high R 2 values obtained from the pseudo-first-order kinetic model suggest that physical interactions, such as pore filling, hydrogen bonding, and hydrophobic interactions, also likely contribute to PFAS removal by biochars.…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…For example, Zhang et al observed a blue-shift of nonaromatic ketone (C=O) peaks and new bands that were assigned to −CF 2 – before and after PFAS sorption by biochars using Fourier transform infrared spectrometry analysis. Similarly, density functional theory calculations confirmed that the C=O groups had the highest adsorption energy for PFAS . Nevertheless, high R 2 values obtained from the pseudo-first-order kinetic model suggest that physical interactions, such as pore filling, hydrogen bonding, and hydrophobic interactions, also likely contribute to PFAS removal by biochars.…”
Section: Resultsmentioning
confidence: 82%
“…Similarly, density functional theory calculations confirmed that the C=O groups had the highest adsorption energy for PFAS . Nevertheless, high R 2 values obtained from the pseudo-first-order kinetic model suggest that physical interactions, such as pore filling, hydrogen bonding, and hydrophobic interactions, also likely contribute to PFAS removal by biochars. The measured contact angles of the commercial biochar and Douglas Fir 900 biochar were 135.3 and 145.5°, respectively, indicating that both PFAS and biochar had a great hydrophobicity and hydrophobic interaction, which was one of the factors facilitating PFAS sorption by biochars …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations